CO adsorption behavior on decorated Pt@Au nanoelectrocatalysts : a combined experimental and DFT theoretical calculation study - Yu, Yaolun (2013)
CO stripping experiments were carried out on a series of submonolayer decorated Pt@Au/C electrocatalysts with different Pt surface coverages which were synthesized by the Cu underpotential deposition (UPD)-Pt redox replacement technique. Combined with density functional theory calculations, the correlation between the CO adsorption strength and surface morphology of the catalyst is well illustrated. Results showed that whether the surface Pt atom could form a PtPt surface ensemble with another neighboring Pt atom is critical, which determines CO adsorption and oxidation behaviors on the electrocatalyst.